Shallow geophysical exploration at the ancient maritime Maya site of Vista Alegre, Yucatan Mexico. (June 2018) - Jaijel, Roy; Kanari, Mor; Glover, Jeffrey B.; Rissolo, Dominique; Beddows, Patricia A.; Ben-Avraham, Zvi; Goodman-Tchernov, Beverly N.
Abstract: Geophysical methods are of great value when investigating or searching for archaeological sites because of their ability to cover a large area in a short time and reveal features and aspects of unexcavated locations. In submerged archaeological sites, the use of seismic survey methods is especially important, as the excavation process is more complicated than at typical terrestrial sites. While the terrestrial portion of the maritime Maya site of Vista Alegre, located in the northeastern part of the Yucatan Peninsula, has been mapped and partially excavated, the shallow offshore flooded landscape has not, in part due to difficulties determining the best targets for initiating the effort. Results from an earlier sediment core campaign resolved the character, environmental associations, and ages of underlying sediments, but could only minimally predict the presence of laterally continuous features due to the distance between cores. To resolve this issue, a seismic survey was conducted to extrapolate the spatial extent of these strata. The survey area covered the flooded bays flanking the terrestrial portion of Vista Alegre. This area has been affected by sea-level rise throughout time, and was a likely location of maritime activity in the past. Results from this study provided laterally continuous evidence for sea-level rise, reinforcing the previous study; and also identified the presence of a submerged ridge-basin structure. This structure was unexpected because it was neither continuous nor congruous with natural trends observed terrestrially. This uniqueness could be attributed to significant differences in the submerged landscape, and possibly the presence of anthropogenically-altered offshore features. The interpreted seismic data is useful both for a site-scale spatial understanding of the flooded landscape history, as well as for identifying potential locations for shallow water archaeological excavations. Highlights: Seismic Survey efficiency in very shallow submerged archaeological sites Locating areas of marine archaeological excavation potential Buried Ridge-Basins structure identified under sediment cover. Evidence of sea level rise in the seismic data